Improving Students’ Creativity In Writing Recount Text by Using Mind Mapping - Cynthia Laksmi Dewi (Manajemen Pendidikan, 2017)
This study is conducted to identify the students’ creativity improvement in writingrecount text in which mind-mapping is implemented in the writing class at the tenth grade of SMA Batik 2 Surakarta in the academic year of 2014/2015. By implementing mind-mapping, the students are actively involved in the teaching learning process. With the involvement, the students have more opportunities in conveying their ideas. The opportunities given improve their critical thinking and innovation. The research was conducted from July to December 2014. The method used in this research was classroom action research. There are two cycles conducted. Every research cycle consisted of planning, acting, observing, and reflecting. These phases are cyclical so that the researcher can refer back to the first phase after completing the last phase. There are qualitative and quantitative data collected in this research. The qualitative data were collected by observing while the quantitative data were collected by designing tests. The findings showed that the implementation of mind-mapping could improve students’ creativity in writing recount text. The critical thinking (from 57.89% to 86.84%), innovation (from 39.47% to 76.31%), and the learning outcome improved. Based on the improvement, it can be concluded that the result of mindmapping implementation is positive.